(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Based on some findings that some plants are tolerant to contaminated media, this research was conducted to study more thoroughly about characters and potencies of some of them as hyperaccumulators. Three of the most tolerant plants were studied in this research i.e Centrocema pubescence, Calopogonium mucunoides,and Micania cordata. The plants were grown in different waste media, i.e. tailing from PT. Aneka Tambang (ANTAM) and people mine waste. Both waste have different characters, physically and chemically. Waste of PT ANTAM major contaminant was cianide (Cn) whereas people mine waste major contaminant was mercury (Hg). This different characters resulted in different plant responses. The plants grown under PT ANTAM waste media gave better performance than that grown under people mine waste media. The most tolerant species was C. pubescence followed by M. cordata and C. mucunoides. Ability in metal accumulation of C. mucunoides was the highest, followed by M. cordata and C. pubescence.The results raised some-prospects for phytoremediation technology for rehabilitating contaminated mined lands. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: Centrocema pubescence, Calopogonium mucunoides, Micania cordata, hyperaccumulators, phytoremediation